KEY INDICATORS OF THE ECONOMIC ACTIVITY OF EDUCATIONAL INSTITUTIONS: MODELING AND PROSPECTS - Nikolaevna Samylina, Yulia; Arkadievich Kishko, Vladimir; Petrovich Filinov, Vladimir; Malysheva, Elena Nikolaevna (Revista Inclusiones, 2020)
The results of activities in the field of education appear in the form of service and, as a rule, do not have a clearly expressed material form. The measurement of the economic activity of educational institutions requires a clear definition of the main categories and values necessary for its calculation. It is necessary to evaluate the economic activity and the rationality of the cost of resources for any purpose based on certain criteria. The article analyses the scientific literature on the problem of determining indicators of the economic activity of educational institutions. Based on an expert survey, the principles of building a system of indicators characterizing economic activity at a university have been defined, analytical support for the assessment of economic activity of university departments has been developed, and the sequence of determining the economic rating of departments of a higher education institution on the basis of the performance indicator has been presented.